2016
DOI: 10.15376/biores.11.3.7839-7848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Refining on Physical Properties and Paper Strength of Pinus massoniana and China Fir Cellulose Fibers

Abstract: aTo obtain a suitable refining process for Pinus massoniana cellulose fibers (PMCF) and China fir cellulose fibers (CFCF), the effects of the beating gap and the pulp consistency on the physical properties and the morphology of the two cellulose fibers were investigated. The results showed that the physical properties of the PMCF and the CFCF were well affected by the beating gap and the pulp consistency. The CFCF showed a smaller weight-average length and width than that of the PMCF. The CFCF exhibited smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Hook., Larixgmelinii (Rupr.) Kuzen., Eucalyptus robusta Smith, Pinus massoniana Lamb., and so on, all of which usually contain a high content of juvenile wood, along with numerous defects such as loose texture, low density, low strength, poor corrosion resistance, and inflammability [1][2][3][4], so it is especially important to conduct functional improvement of fast-growing woods in plantations. Wood modification methods mainly include acetylation, impregnation, compression, fire-retarding, and heat treatment, among which heat treatment-assisted wood modification has been extensively studied [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Hook., Larixgmelinii (Rupr.) Kuzen., Eucalyptus robusta Smith, Pinus massoniana Lamb., and so on, all of which usually contain a high content of juvenile wood, along with numerous defects such as loose texture, low density, low strength, poor corrosion resistance, and inflammability [1][2][3][4], so it is especially important to conduct functional improvement of fast-growing woods in plantations. Wood modification methods mainly include acetylation, impregnation, compression, fire-retarding, and heat treatment, among which heat treatment-assisted wood modification has been extensively studied [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…These spaces were scarce in the refined pulps, so the light crossed only the cell wall with lower diffraction (Biermann 1996). The opacity reduction with the refining increment was reported for grass (Andrade & Colodette 2016), softwood (Chen et al 2016(Chen et al , 2017 and hardwood (Zanuncio et al 2016, Pupo et al 2019 pulps.…”
Section: Physical-mechanical Pulp Properties After Bleachingmentioning
confidence: 74%
“…Refining increased the number of fiber connections in one stage but also degraded them in a later stage; the tensile index and bursting strength were related to the connection between the fibers, whereas the tear index was related to fiber morphology (Gharehkhania et al 2015). The tear index was reduced at lower refining levels in softwood pulps, as reported for Pinus massoniana and China fir (Chen et al 2016). This index in hardwood pulps increased at the first refining level due to the increase in the number of connections and decreased at higher levels due to fiber degradation (Gharehkhania et al 2015), as reported for Corymbia citriodora (Severo et al © Forest Research Institute Malaysia 2013) and Eucalyptus grandis × Eucalyptus urophylla (Zanuncio et al 2016).…”
Section: Physical-mechanical Pulp Properties After Bleachingmentioning
confidence: 77%
“…When the activator is formulated as a solution, although the flax fibers exhibit an excellent adsorption property, it is still difficult for activator to enter and disperse evenly in the fibers due to the poor accessibility of the untreated fibers, which directly leads to a low activation effect, resulting in a low electrochemical performance of the prepared carbonized materials. Refining, a commonly used process in papermaking (Marrakchi et al 2011;Mao et al 2019), improves the physical properties of pulp fibers, including their structure and size, and further improves their specific surface area and swelling performance (Chen et al 2016;Motamedian et al 2019). During refining the wet cellulosic fibers are repeatedly compressed and sheared, resulting in internal delamination of the cell walls, and increased swelling in the wet state.…”
Section: Introductionmentioning
confidence: 99%